Coleman-Weinberg Abrikosov-Nielsen-Olesen strings - Eto, Minoru; Hamada, Yu; Jinno, Ryusuke; Nitta, Muneto; Yamada, Masatoshi (Arxiv, 2022)
We study properties of Abrikosov-Nielsen-Olesen (ANO) strings with the Coleman-Weinberg (CW) potential, which we call CW-ANO strings. While the scale-invariant scalar potential has a topologically trivial vacuum admitting no strings at the classical level, quantum correction allows topologically nontrivial vacua and stable string solutions. We find that the system of the CW potential exhibits significant difference from that of the conventional Abelian-Higgs model with the quadratic-quartic potential. While a single-winding string is qualitatively similar in both systems, and the static intervortex force between two strings at large distance is attractive/repulsive in the type-I/II regime for both, that between two CW-ANO strings exhibits a nontrivial structure. It develops an energy barrier between them at intermediate distance, implying that the string with winding number > 1$ can constitute a metastable bound state even in the type-II regime. We name such a superconductor type-$\overline{1.5}$. We also discuss implications to high-energy physics and cosmology.
Gesehen am 17.10.2022